Pengembangan Modul Pembelajaran Matematika Berbasis Brain Based Learning (Bbl) Menggunakan Permainan Teka-Teki Silang - Alma Mujahida; Muhamad Firdaus; Rahman Haryadi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The aim of this research is to determine the feasibility of developing a brain-based learning mathematics module using crossword puzzle games as seen from the level of validity, practicality, and effectiveness. The method used is research and development with the ADDIE research design. This research was conducted at SMPN 11 Sungai Ambawang with test subjects of 27 class VIII students. The validity results show that media validation reached a percentage of 83.33% and material validation was 89.98% in the